The Knowledge on Autism Spectrum Disorder among Preschool Teachers in selected Schools - Shrestha, Rhinu; Dhakal, Swikri (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder. Lately, prevalence of ASD is increasing alarmingly . There is a need of adequate knowledge of ASD among preschool teachers as they are expected to play a crucial role in early detection. The objective of the study was to assess the knowledge of ASD among preschool teachers of selected schools of Budhanilakantha. Methods: A descriptive cross-sectional study was conducted using total enumeration method among 105 preschool teachers of Budhanilakantha-10. The study was conducted from 2080-9-15 to 2080-9-29. Data analysis and interpretation were done using inferential statistics and presented in tabulated form. Results: More than half (54.3%) of preschool teachers had inadequate knowledge ,while less than half (45.7%) of the population had adequate knowledge regarding ASD. Level of knowledge of respondents was found significantly associated with type of school (p = 0.038), training (p = 0.028) and exposed to autistic child (p<0.001). Conclusion: The level of knowledge on ASD among Preschool teachers of Budhanilakantha municipality was inadequate. The level of knowledge was influenced by exposure, training and type of school. Therefore, training, inservice education, workshops and seminars regarding ASD are suggested to teachers to identify and assist in proper management of autism.